Preparation and modification of high dietary fiber flour: A review. (November 2018) - Zhang, Huijuan; Wang, Hongna; Cao, Xinran; Wang, Jing
Abstract: Dietary fiber, consisting of soluble dietary fiber and insoluble dietary fiber, has beneficial functional effects on the human body that are receiving increasingly attention. Refined flour lacks dietary fiber and poses potential risks to human health. Therefore, improving the nutritional value and processing performance of flour in the preparation and modification of high dietary fiber flour is of great importance. Whole-wheat flour, a high dietary fiber flour obtained by crushing whole-wheat grains, is rich in nutritional value. High dietary fiber flour obtained by adding bran back into the flour makes full use of the bran, which increases the utilization of wheat-milling byproducts. The addition of dietary fiber to flour is a direct method for obtaining high dietary fiber flour, and which has evolved with the development of the dietary fiber extraction industry. Further modifications of whole-wheat flour, bran, and dietary fiber, such as milling, extrusion, heat treatment, and biological treatment, can diminish the effect that bran materials on the quality of flour and flour products. This review summarizes methods used for the preparation and modification of three kinds of high dietary fiber flour and the effects of these different methods on the quality of flour and flour products, with the aim to provide guidance for the industrial preparation of high dietary fiber flour. Graphical abstract: Highlights: Adding bran or dietary fiber (DF) back into flour can obtain high DF flour. Physical, chemical, and biological methods have been used to modify bran. Characteristics of gluten, dough, and products are the main evaluation standards.